1986
DOI: 10.1080/00071668608416906
|View full text |Cite
|
Sign up to set email alerts
|

Packed cell volume of blood from male domestic chicks

Abstract: The packed cell volumes of blood from healthy chicks of domesticated fowl were required for studies on avian malaria and data were specially generated under standardised conditions. The mean packed erythrocyte volume for chicks 15 to 43 d old (34 males of two egg laying breeds) was 28.7% (range 23 to 39%). The 95% confidence limits for a single reading in a healthy chick were 24.6 to 32.9%. Therefore, a value of less than or equal to 24% is regarded as subnormal and a value of greater than or equal to 33% is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In birds that did not succumb, this colour disappeared from the droppings when the parasitaemia became negative and the haematocrit value simultaneously returned to normal. The normal haematocrit values in healthy young male birds of those breeds used here ranged from 25% to 32% (Williams, 1986a), rather more limited than that recorded for adult fowl by Freeman (1971a) of 20% to 40%, and unexpectedly falling within the range of 20% to 30% given for female chickens (Freeman, 1984) */ while being quite distinct from the range of 40% to 45% of males (Freeman, 1984). The difference may be due to an age factor.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In birds that did not succumb, this colour disappeared from the droppings when the parasitaemia became negative and the haematocrit value simultaneously returned to normal. The normal haematocrit values in healthy young male birds of those breeds used here ranged from 25% to 32% (Williams, 1986a), rather more limited than that recorded for adult fowl by Freeman (1971a) of 20% to 40%, and unexpectedly falling within the range of 20% to 30% given for female chickens (Freeman, 1984) */ while being quite distinct from the range of 40% to 45% of males (Freeman, 1984). The difference may be due to an age factor.…”
Section: Discussionmentioning
confidence: 89%
“…For comparative purposes, a further 34 healthy control chickens of the same breeds and ages were kept under the same conditions, but they were not infected. Based on the results obtained from the uninfected controls, the normal haematocrit range was judged to be from 25% to 32% (Williams, 1986a). Nevertheless, 5% of single haematocrit readings from healthy chickens might be expected to fall outside that range.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Javed (Javed 2003) reported that hematological parameters studied there is no significant differences between treatment and control groups in hemoglobin concentration and total erythrocyte count. Williams (Williams 1986) carried out an experiment in 34 male domestic chicks of 21 days old to study packed cell volume. He found that the mean packed cell volume was 28.7 percent with range from 23 to 39 percent.…”
Section: Effects On Hematological Parametersmentioning
confidence: 99%